2015
DOI: 10.3139/113.110365
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Virtual Washing Machine

Abstract: In the past years some researches were conducted to model laundryw ashing in the automatic washing machine.T he most studies,h owever,w ere focused to some aspects of the automatic laundryw ashing (e.g.s pinning cycle)a nd not on the washing process as whole.I nt his paper am odel of aw ashing machine is presented that is based on measured data of 9different washing machines with rated capacityb etween 5kga nd 11 kg,w hich are produced by six different manufacturers.T he proposed approach is based on multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, we compared the average used in this study with the one reported by Lasic et al (2015) and found them consistent (both 1.7 g CO 2− eq/g detergent). Other sources of uncertainty and variability related to the detergent dataset were not considered in this study, such as the manufacturing processes, sourcing of raw materials, and sources of energy used for manufacturing.…”
Section: Variability and Uncertaintymentioning
confidence: 96%
“…However, we compared the average used in this study with the one reported by Lasic et al (2015) and found them consistent (both 1.7 g CO 2− eq/g detergent). Other sources of uncertainty and variability related to the detergent dataset were not considered in this study, such as the manufacturing processes, sourcing of raw materials, and sources of energy used for manufacturing.…”
Section: Variability and Uncertaintymentioning
confidence: 96%
“…Lasic and Stamminger [12] have also shown the way in which consumers must change their laundry washing behaviour when using washing machines with a high-rated capacity. They simulated the effect of deferring the wash unless a sufficient volume of load to fill (almost) the rated capacity of a large washing machine at a certain washing condition can be utilised.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the average temperature of the washes is different to the temperature, which is the basis for the declaration (which is five times a cotton wash at a 60°C programme and two times a cotton wash at a 40°C programme, which gives a simple average of a nominal 54.3°C). This difference to the real‐life average nominal washing temperature is considered to have a linear effect of 0.020 kWh/K on the energy needed (Lasic et al ., – formula (6)). Real‐life average nominal temperatures are known from the same consumer survey in 11 European countries plus Turkey .…”
Section: Methodsmentioning
confidence: 99%